VLN2 Regulates Plant Architecture by Affecting Microfilament Dynamics and Polar Auxin Transport in Rice. Issue 10 (20th October 2015) - Wu, Shengyang; Xie, Yurong; Zhang, Junjie; Ren, Yulong; Zhang, Xin; Wang, Jiulin; Guo, Xiuping; Wu, Fuqing; Sheng, Peike; Wang, Juan; Wu, Chuanyin; Wang, Haiyang; et al.
Abstract : A rice VILLIN2 mutant, with altered microfilament dynamics, displays malformed organs associated with weakened membrane localization of the PIN2 protein and reduced polar auxin transport. Abstract: As a fundamental and dynamic cytoskeleton network, microfilaments (MFs ) are regulated by diverse actin binding proteins (ABPs). Villins are one type of ABPs belonging to the villin/gelsolin superfamily, and their function is poorly understood in monocotyledonous plants. Here, we report the isolation and characterization of a rice ( Oryza sativa ) mutant defective in VILLIN2 ( VLN2 ), which exhibits malformed organs, including twisted roots and shoots at the seedling stage. Cellular examination revealed that the twisted phenotype of the vln2 mutant is mainly caused by asymmetrical expansion of cells on the opposite sides of an organ. VLN2 is preferentially expressed in growing tissues, consistent with a role in regulating cell expansion in developing organs. Biochemically, VLN2 exhibits conserved actin filament bundling, severing and capping activities in vitro, with bundling and stabilizing activity being confirmed in vivo. In line with these findings, the vln2 mutant plants exhibit a more dynamic actin cytoskeleton network than the wild type. We show that vln2 mutant plants exhibit a hypersensitive gravitropic response, faster recycling of PIN2 (an auxin efflux carrier), and altered auxin distribution. Together, our results demonstrate that VLN2 plays an important role in regulating plant architecture by modulating MF dynamics, recycling of PIN2, and polar auxin transport.